Pengaruh affetcive commitment terhadap organizational citizenship behavior melalui work engagement - Rahman, Annisa Alifia; Frianto, Agus (Jurnal Ilmu Manajemen, 2024)
PT. X is a company that operates in engineering, procurement, construction, and fabrication, where employees have quite heavy tasks. Companies need to ensure that their employees have a solid affective commitment to maximizing organizational citizenship behaviour in the company so that productivity will continue to be maintained. This study aims to test and analyze the effect of affective commitment on organizational behaviour through work engagement on employees of the steel structure division at PT. X. This study aims to test and analyze the effect of affective commitment on organizational behaviour through work engagement on employees of the steel structure division at PT. X. The sampling technique used is non-probability sampling, specifically total sampling, in which all population members are sampled, with 41 respondents of the steel structure division employees at PT. X. The statistical analysis used in this research is partial least squares (PLS) with the help of SmartPLS 4.1.0.0 software. The results of this study explain that affective commitment has a significant positive effect on organizational behaviour, affective commitment has a significant positive effect on work engagement, work engagement has a significant positive effect on organizational citizenship behaviour, and work engagement successfully mediates the relationship between affective commitment and organizational citizenship behaviour. This research implies that PT. X needs to increase employees’ affective commitment by strengthening the emotional relationship between employees and the company to maximize organizational citizenship behaviour in the workplace so that employees are more sincere in helping each other.